Rezolvati in Z ecuatiile: a) 3(x-4) +2=5x; b) 4x-20=-5(x+1) +3; c) -4(2-x) -3x=2x-5; d) 2(4x-3)-7x+2=3x-12; e) 4(x+2) - (2x-14)=3(5-2x)-1; f) 5(3x+4) + 2(x-7)=3(5x-2); g) 7(2x-1)+3(7-4x)-15=x-8; h) 5(x-4)-4(x-5)+3x-7=8(x-3)+1; i) 2(4x+2)-7(x+1)=3(3-2x)+12x; j) 1-3(x+6)-2(5x-4)=4(3x-14)-3.

2

Răspunsuri

2014-05-26T19:37:58+03:00
A)3×(x-4)+2=5x
3x-12+2=5x
3x-5x=12-2
-2x=10
x=10:(-2)
x=-5
b) 4x-20=-5 (x+1)+3
4x-20=-5x-5+3
4x+5x=20-5+3
9x=18
x=18:9
x=2
c)-4×(2-x)-3x=2x-5
-8+4x-3x=2x-5
4x-3x-2x=8-5
-x=3|×(-1)
x=-3
Multumesc! Ma puteti ajuta va rog frumos cu toate rezolvarile?
2014-05-26T19:55:29+03:00
a) 3(x-4) +2=5x;=> 3x-12+2=5x => 3x-5x=10=> 2x=10  x=5
b) 4x-20=-5(x+1) +3;=>4x-20=-5x-5+3=> 4x+5x=20-5+3=>9x=18=>x=2
c) -4(2-x) -3x=2x-5; => -8+4x-3x=2x-5=> x-2x=8-5=>-x=3=> x=-3
d) 2(4x-3)-7x+2=3x-12=>8x-6-7x+2=3x-12=>x-3x=-8=> -2x=-8=> x=4
e) 4(x+2) - (2x-14)=3(5-2x)-1; =>4x+8-2x+14=15-6x-1=>8x=-22+15-1=> 8x=8   x=1
f) 5(3x+4) + 2(x-7)=3(5x-2);=>5x+20+2x-14=15x-6=>2x=-12  x=-6
g) 7(2x-1)+3(7-4x)-15=x-8;=> 14x-7+21-12x-15=x-8 => x=-7
h) 5(x-4)-4(x-5)+3x-7=8(x-3)+1; =>5x-20-4x+20+3x-7=8x-16+1=>-4x=-8=>x=2
i) 
2(4x+2)-7(x+1)=3(3-2x)+12x=> 8x+4-7x-7=9-6x+12x=>-5x= 12=> x=-12 supra 5
j) 1-3(x+6)-2(5x-4)=4(3x-14)-3=>1-3x-18-10x+8=12x-56-3=>-9-13x=12x-59=> -25x=-50
                                                                                                               x=2